Facile synthesis of silica nanoparticles grafted with quaternized linear, comblike and toothbrushlike copolymers1. Issue 14 (14th April 2015) - Guo, Yanfei; Liu, Huanhuan; Tang, Dandan; Li, Cangxia; Zhao, Youliang
<x xml:space="preserve">Abstract</x> The alkoxysilane–hydroxyl coupling reaction, quaternization and RAFT polymerization were combined to synthesize three types of quaternized copolymers grafted silica with thermo-dependent surface wettability.